Religion and state: the Muslim approach to politics - Brown, Leon Carl (Columbia Univ. Press, 2000)
PART ONE: THE HERITAGE: Setting the stage: Islam and Muslims -- Islam, Judaism, and Christianity in comparative perspective: an overview -- Muslim "church government" -- The historical bases of traditional Muslim and Christian political theory -- Unity and community -- The roots of political pessimism -- Muslim attitudes toward the state: an impressionistic sketch -- PART TWO: CONVULSIONS OF MODERN TIMES: Islam and politics in modern times: the great transformation -- Meeting the Western challenge: the early establishment response -- The early antiestablishment response to the Western challenge -- From World War I to the 1960s: the years of muted Islamist politics -- The return of Islam? -- The radical Muslim discourse -- Al-Banna, Mawdudi, and Qutb -- Khomeini and the Shi'ite Islam -- Conclusion -- Islam and politics past and present: a bibliographical essay